Är gnagare reservoar för patogena leptospiraarter i Sverige? - Gammelgård, Erik (SLU/Dept. of Clinical Sciences (until 231231), 2009)
The aim of the project was to investigate if Swedish rodents, brown rat (Rattus norvegicus), house mouse (Mus musculus), wood mouse (Apodemus spp) and water vole (Arvicola terrestris) captured in pig herds and in urban areas, constitute a reservoir for pathogenic Leptospira spp. Under Swedish conditions leptospirosis gives rise to reproductive disorders in pigs and symptoms of flu in humans. It has long been established that rodents are chronic carriers of pathogenic leptospires in their kidneys, and can spread the bacteria with urine. The old nomenclature of serovoars is still in use, but a new system of genetic classification has developed and today the genus Leptospira contains 17 species. There are several diagnostic test developed for leptospirosis. Serology and culture are used today in Sweden by Swedish Institute for Infectious Disease Control and Swedish National Veterinary Institute. Over the last decade the molecular method Polymeras Chain Reaction (PCR) has been developed. PCR was chosen as the method to detect leptospires, for the first time in Sweden. The problem was that the PCR-system available could not separate between patogenic species. Two conventional PCR-systems, Lig PCR and Adia PCR, developed to detect pathogenic Leptospira spp. in kidney tissue were used. The material were 116 kidneys from Swedish rodents that were captured in 11 places, between the years 2005 to 2007, during an ongoing PhD projekt. Adia PCR detected 15 samples that most likely were pathogenic leptospires. PCR-products were sent for sequencing to Swedish National Veterinary Institute. Sequencing of PCR-products comfirmed that nine of the 15 DNA sequences belonged to potentially pathogenic Leptospira spp. The DNA sequences were most similar to L. borgpetersenii, L. weili and L. interrogans serovar copenhageni. Among remaining PCR-products a part of the ninth house mice chromosome was identified. Lig PCR did not work satisfactorily, and no samples were sent in to Swedish National Veterinary Institute for DNA sequencing. It was concluded that Adia PCR could detect pathogenic leptospires in kidney tissue of rodents and the Swedish rodents constitute a reservoir for pathogenic Leptospira spp.